OPERATIONAL RISK ANALYSIS IN ISLAMIC BANKING: A CASE STUDY IN INDONESIA - Prabowo, agus P; Anggraini, Tuti (Universitas Islam Lamongan, 2024)
This study analyzes operational risk in Islamic banking in Indonesia, focusing on identifying the types of operational risks faced and strategies to manage them. Operational risks cover a wide range of issues such as human error, system failure, and non-compliance with sharia regulations and principles. The study utilized a qualitative approach through in-depth interviews with risk and internal audit managers from several leading Islamic banks in Indonesia. The results show that the most significant operational risks in Islamic banking in Indonesia are human error risk, information technology failure, and sharia compliance risk. To address these risks, Islamic banks have implemented various strategies such as improving internal controls, training and developing human resources, and investing in information technology. In addition, compliance with sharia regulations and principles is also improved through monitoring regulatory changes and implementing strict sharia compliance policies. The study also found that adaptation to economic and social changes is an important factor in enhancing the resilience of Islamic banking. Islamic banks in Indonesia develop the capacity to respond to changes quickly through monitoring economic and social trends and developing quick and effective responses. In conclusion, with the implementation of comprehensive and integrated strategies, Islamic banking in Indonesia can significantly reduce operational risk and increase its resilience to economic and social changes, thereby providing better services to customers and ensuring sustainable growth.